Interpretasi Ayat-Ayat Gender Perspektif Islam Liberal Tentang Kepemimpinan Politik Perempuan - Chalik, Abdul (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2015)
For several decades, the role of Muslim female in political arena is limited and still dominated by Muslim male figures. Religious doctrines seem to take part in constructing women into social life. Women are still perceived as secondary person before men, having much emotional feelings, and incapable to handle such social problems. It has been much demonstrated by traditional scholars that the providence of men is being a leader, having much power, and is rightly superior to women. In this case, contemporary feminist Muslim such like Fatima Mernissi, Riffat Hassan, Asghar Ali Engineer, and Fazlur Rahman has contended this notion. They argue that there was possibly different impression on the interpretation of Qur’an that affects Qura’nic worldview towards the existence of women. According to them, Qur’an was precisely revealed to liberate women from social subjection. This article scrutinizes methodological framework in establishing a new light of understanding Qur’anic verse on women, especially on the issues on the origins of women creature, leadership, attestation and the right for inheritance.